Microplastics in yellowfin tuna (Thunnus albacares) entrails from General Santos City, South Cotabato, Philippines. - Junio, Ma. Rose Ann S.
The entails of yellowfin tuna (Thunnus albacares) from General Santos Fish Port Complex were studied for the presence of microplastics. Through physical analysis using Rose Bengal staining as well as observation under the stereomicroscope, results revealed the presence of suspected microplastic (MPs) particles in the different visceral samples, namely gut content, stomach stomach mix, and other entrails. The gut content of the tuna showed the highest number of MPs detected (16.6 ± 13.58) while lowest count was noted in the other tuna entrails (0.2 ± 0.45). There is a significant difference in the microplastic occurrence among the samples tested. When evaluated and characterized under the stereomicroscope using stage micrometers, the suspected MPs consist of plastic pellets and fragments which were the most dominant microplastics present in the viscera, with sizes ranging from 40 μm to 400 μm. To verify and further characterize the chemical composition and the polymer types of the suspected microplastics, the particles were subjected to Fourier Transform Infrared Spectrophotometer (FTIR) with a spectra of 500-4000 cm-1. The results of the FTIR analysis revealed the presence of MPs in the sample, with polyethylene (66.80%) as the main type of plastic polymer present in the stomach and other entrails, and cellophane in the gut content (48.64%) and in the stomach mix (45.29%). This study provides insights on the presence of microplastics in the entrails of yellowfin tuna and the hazards associated with these MPs, since these entrails are presently being used as main raw material in the processing of different fermented foods and non-food products in the country.